The protective role of cannabidiol in stress-induced liver injury: modulating oxidative stress and mitochondrial damage - Huang, Chengyu; Liang, Huichao; Liang, Xiaohua; Liu, Yueyi; Wang, Jiaoling; Jiang, Haoran; Kou, Xinhui; Chen, Jun; Huang, Lili (Frontiers in Pharmacology, 2025)
BackgroundStress-induced liver injury, resulting from acute or chronic stress, is associated with oxidative stress and inflammation. The endocannabinoid system, particularly cannabinoid receptor 2 (CB2R), plays a crucial role in liver damage. However, there are currently no clinical drugs targeting CB2R for liver diseases. Cannabidiol (CBD), a CB2R agonist, possesses anti-inflammatory and antioxidant properties. This study aims to investigate the pharmacological effects of CBD in a mouse model of stress-induced liver injury.MethodsWe employed a mouse model of stress-induced liver injury to evaluate the protective effects of CBD. Assessments included histopathological analysis, cytokine detection via ELISA, protein expression analysis using immunohistochemistry and Western blot, and gene transcription differential analysis. Transmission electron microscopy was utilized to observe mitochondrial morphology. Additionally, we examined the expression levels of CB2R, SLC7A11, α-SMA, and ACSL4 proteins to elucidate the mechanisms underlying CBD’s effects.ResultsCBD exhibited significant protective effects against stress-induced liver injury in mice. Decreases in liver function indicators (including Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT)) and inflammatory cytokines (such as IL-1β and Tumor Necrosis Factor-alpha (TNF-α)) were observed. CBD enhanced CB2R expression and reduced α-SMA levels, mitigating liver fibrosis. It also decreased ACSL4 levels, increased SOD and GSH-Px activities, and upregulated SLC7A11 protein expression. Furthermore, CBD improved mitochondrial morphology, indicating a reduction in oxidative cell death.ConclusionCBD activates the CB2R/α-SMA pathway to modulate liver inflammation and fibrosis. Through the SLC7A11/ACSL4 signaling pathway, CBD alleviates oxidative stress in stress-induced liver injury, enhances mitochondrial morphology, and reduces liver damage. These findings provide a theoretical basis for the potential application of CBD in the prevention and treatment of stress-induced liver injury.